HUBUNGAN ERGONOMI DENGAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEKERJA DI CV X KOTA MALANG - Wisty Claudya; Beni Hari Susanto; Septia Dwi Cahyani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Occupational health and safety (K3) aims to protect workers from occupational diseases. One of the occupational diseases that can appear at any time is Musculoskeletal Disorder (MSDs). Musculoskeletal Disorder complaints are caused by ergonomic factors, namely the wrong working posture. The purpose of this study was to determine the relationship between ergonomics and Musculoskeletal Disorder complaints among workers at CV. X City of Malang. The research design used observational analytic with a cross-sectional approach. The sample in this study consisted of 36 respondents with using random sampling technique based on inclusion and exclusion criteria. Analysis of the results of the study used the Spearman rank test to determine the relationship between ergonomics and Musculoskeletal Disorder Complaints. Based on the results of the study, it was found that the risk data for sitting work postures of respondents got 9 people with high results and 27 people with moderate results. While the results of respondents who experienced high Musculoskeletal Disorder were 12 people and those who experienced moderate Musculoskeletal Disorder were 24 people. The results showed that there was a significant relationship between work posture and complaints of Musculoskeletal Disorders (p=0.000<0.05) and there was a relationship between length of work and complaints of Musculoskeletal Disorders (p=0.000<0.05). It can be concluded that there is a relationship between working posture and length of work on Musculoskeletal Disorder complaints among workers at CV. X City of Malang. Occupational health and safety (K3) aims to protect workers from occupational diseases. One of the occupational diseases that can appear at any time is Musculoskeletal Disorder (MSDs). Musculoskeletal Disorder complaints are caused by ergonomic factors, namely the wrong working posture. The purpose of this study was to determine the relationship between ergonomics and Musculoskeletal Disorder complaints among workers at CV. X City of Malang. The research design used observational analytic with a cross-sectional approach. The sample in this study consisted of 36 respondents with using random sampling technique based on inclusion and exclusion criteria. Analysis of the results of the study used the Spearman rank test to determine the relationship between ergonomics and Musculoskeletal Disorder Complaints. Based on the results of the study, it was found that the risk data for sitting work postures of respondents got 9 people with high results and 27 people with moderate results. While the results of respondents who experienced high Musculoskeletal Disorder were 12 people and those who experienced moderate Musculoskeletal Disorder were 24 people. The results showed that there was a significant relationship between work posture and complaints of Musculoskeletal Disorders (p=0.000<0.05) and there was a relationship between length of work and complaints of Musculoskeletal Disorders (p=0.000<0.05). It can be concluded that there is a relationship between working posture and length of work on Musculoskeletal Disorder complaints among workers at CV. X City of Malang. Kesehatan dan keselamatan kerja(K3) bertujuan untuk melindungi pekerja dari penyakit akibat kerja. Salah satu penyakit akibat kerja yang dapat muncul sewaktu waktu adalah Muskuloskeletal Disorder (MSDs). Keluhan Muskuloskeletal Disorder diakibatkan oleh faktor ergonomi, yaitu postur kerja yang salah. Tujuan dari penelitian ini untuk mengetahui hubungan ergonomi dengan keluhan Musculoskeletal Disorder pada pekerja di CV. X Kota Malang. Desain penelitian ini menggunakan analitik observasional dengan pendekatan cross sectional. Sampel pada penelitian ini terdiri dari 36 responden dengan menggunakan teknik random sampling berdasarkan kriteria inklusi dan eksklusi. Analisa hasil penelitian menggunakan uji rank Spearman untuk mengetahui hubungan ergonomi dengan Keluhan Muskuloskeletal Disorder. Berdasarkan hasil penelitian ditemukan data risiko postur kerja duduk responden mendapatkan hasil tinggi sebanyak 9 orang dan hasil sedang sebanyak 27 orang. Sementara hasil dari responden yang mengalami Musculoskeletal Disorder tinggi sebanyak 12 orang dan yang mengalami Musculoskeletal Disorder sedang sebanyak 24 orang. Hasil penelitian menunjukan bahwa terdapat hubungan yang signifikan antara postur kerja dengan keluhan Musculoskeletal Disorders (p=0,000<0,05) dan terdapat hubungan lama kerja dengan keluhan Musculoskeletal Disorders (p= 0,000<0,05). Dapat disimpulkan bahwa terdapat hubungan postur kerja dan lama kerja terhadap keluhan Muskuloskeletal Disorder pada pekerja di CV. X Kota Malang.